DIAGNOSING THE NEEDS FOR ENGLISH AT VOCATIONAL SCHOOLS: REDESIGN THE CURRICULUM 2013? - Kusni Kusni; Syamwil Syamwil; Refnaldi Refnaldi (International Conference on Languages and Arts, 2014)
This paper aims at exposing a research finding on critical thoughts of English for vocational school students in 2013 curriculum viewed from the theories of the English for specific purposes (ESP) in which needs analysis should be the basis. The designers of Curriculum 2013 of English seem to neglect that the main objective of the subject by paralleling English for senior high schools with that of the vocational schools. To scientificly prove it, in this research I did needs analysis in two study programs from three different vocational schools, Engineering and Accounting, involving 60 students. Students were given questionnaire, but other respondents were interviewed. The findings of this research mainly show that English subject for the vocational schools was presently an English for general purposes (EGP), not ESP. On the other hand, students of vocational school needs English based on the result of need analysis. Since it is clearly stated by the law that vocational school students should be prepared to enter directly to job markets appropriate to their study program, English for the students should be ESP in which its purposes and materials should be in line to their study program and specialties known through careful and systematic needs analysis. Thus, the findings imply that English for vocational school students should be carefully redesigned and reconsidered before it is widely used all over the nation.   Key words: Needs analysis,  English for specific purposes, 2013 curriculum